An investigation of the validity of the virtual spatial navigation assessment - Ventura, Matthew; Shute, Valerie; Wright, Timothy J.; Zhao, Weinan (Frontiers in Psychology, 2013)
This correlational study investigated a new measure of environmental spatial ability (i.e., large scale spatial ability) called the Virtual Spatial Navigation Assessment (VSNA). In the VSNA, participants must find a set of gems in a virtual 3D environment using a first person avatar on a computer. The VSNA runs in a web browser and automatically collects the time taken to find each gem. The time taken to collect gems in the VSNA was significantly correlated to three oth-er spatial ability measures, math standardized test scores, and choice to be in a STEM (science, technology, engineering, or math) career. These findings support the validity of the VSNA as a measure of environmental spatial ability. Finally, self-report video game experience was also significantly correlated to the VSNA suggesting that video game may improve environmental spatial ability. Recommendations are made for how the VSNA can be used to help guide individuals toward STEM career paths and identify weaknesses that might be addressed with large scale spatial navigation training.